Investigation of soil particle size distribution, physical and chemical properties due to coal mining subsidence - Lu, Akang; Fan, Tingyu; Yang, Changde; Wang, Shun; Wang, Xingming (Frontiers in Earth Science, 2025)
Underground coal mining causes movement of overlying rock layers and damage to geological structures, leading to surface subsidence and the development of tensile cracks. To investigate the influence of surface cracks on soil structure and properties, this study was carried out in the Zhuzhuang Mine subsidence area. The research focused on two typical tensile cracks that segmented the area into three plots (HP, MP, LP), with 105 soil samples collected from around the cracks. By measuring soil particle size distribution (PSD), organic matter (SOM), moisture content (MC), available phosphorus (SAP), and available kalium (SAK), and combining multifractal theory to analyze soil structural heterogeneity. The results indicate that surface fissures promote the formation of preferential flow paths on the slope, leading to the migration of clay particles towards the fissures. The average surface clay content in the HP area is 5.45%, significantly higher than the 3.03% in the LP area. The fractal dimension shows that the fractal dimension of surface soil is lower than that of deep soil, and increases with depth, reflecting that cracks exacerbate the stratification and heterogeneity of soil structure. Correlation analysis further revealed that there was a significant negative correlation (−0.916) and positive correlation (0.903) between the viscosity and powder particles in the HP region and the fractal dimension D(0), while there was a strong negative correlation (−0.992) between the powder particles in the LP region and D(1). There is a positive correlation between soil moisture and clay content, but the nutrient migration path in the LP area is disrupted due to the obstruction of cracks and terrain, resulting in a weakened correlation with particle size. This study elucidates the mechanism by which mining subsidence cracks affect soil physical and chemical properties by altering soil particle transport and water distribution, providing a theoretical basis for land reclamation and ecological restoration in mining areas.